Synthesis of 1-Aza-6,7-dehydrotropanes via Copper(I)-Catalyzed Coupling of 5-Chloropentan-2-one with Hydrazines and Terminal Alkynes - Van Beek, Wim E.; Weemaes, Karel; Herrebout, Wouter A.; Vande Velde, Christophe M. L.; Tehrani, Kourosch Abbaspour (Synlett, 2018)
A one-pot, three-component, Cu(I)-catalyzed coupling of primary hydrazines, 5-chloropentan-2-one, and terminal alkynes was developed. The resulting 1-aza-6,7-dehydrotropanes compose a new class of substances while related 1-azatropanes are scarcely described in literature and closely resemble tropane alkaloids. Hydrogenation of the double bond in 1-aza-6,7-dehydrotropanes triggered a rearrangement, involving a [1,3]-hydride shift, forming cyclic hydrazones.
Keywords: multicomponent reactions; alkynes; hydrazines; ketones; copper catalysis; 1-azatropanes